IMPLEMENTASI TERHADAP STATUS HUKUM, HAK DAN KEDUDUKAN ANAK LUAR KAWIN PASCA KELUARNYA PUTUSAN MAHKAMAH KONSTITUSI TENTANG UJI MATERIL UNDANG-UNDANG PERKAWINAN - Desi Sommaliagustina (Universitas Harapan Medan, 2020)
Since the issuance of the Constitutional Court Decision Number 46 / PUU-VIII / 2010, the contents granted the request of Machica Mochtar who was married to Moerdiono in an Islamic way but was not listed. From the marriage a boy named Muhammad Iqbal Ramadhan was born. After the Constitutional Court's decision was issued, the status of an extramarital child not only had civil relations with his mother and family, but also had civil relations with his father and father's family. MK decisions have broad implications, because children outside of marriage include children born of marriage that are religiously valid but not recorded, and children born from adultery.